Feline oral squamous cell carcinoma: a comprehensive approach to improve treatment outcome - Yoshikawa, Hiroto, author; LaRue, Susan M., advisor; Ehrhart, EJ, committee member; Randall, Elissa, committee member; Thamm, Douglas, committee member (Colorado State University. Libraries, 2013)
To view the abstract, please see the full text of the document.
Keywords: patient immobilization; feline oral squamous cell carcinoma; stereotactic radiation therapy; cancer biology; FDG-PET